China’s engagement in global health governance through cooperation with African states - Rubo, Olesya P. (Journal of the Belarusian State University. International Relations, 2026)
The article examines how Chinese health policy has evolved in the context of global governance by focusing on its cooperation with African states. It analyses the historical development of the China’s health assistance, the evolution of China – Africa cooperation under the Forum on China – Africa cooperation, the Belt and road initiative, and the concept of the health silk road. The article focuses in particular on the political and institutional dimensions of China’s participation in global health governance, including its engagement with the World Health Organisation and regional bodies, especially the African Union. It also reviews the main forms of health cooperation: the deployment of medical teams, the construction and upgrading of health infrastructure, infectious disease control, and support for pharmaceutical production. China’s model of health cooperation combines pragmatic foreign policy interests with a discourse of global solidarity and sustainable development. The article concludes that China is expanding health cooperation with African states through multiple frameworks while presenting this engagement as part of its commitment to multilateral cooperation and the achievement of the Sustainable development goals.